A geometry and optical property inspection system for automotive glass based on fringe patterns - Xu, Jing; Xi, Ning; Zhang, Chi; Shi, Quan; Gregory, John (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
In this paper, an automotive glass inspection system based on fringe patterns is proposed. This system can inspect the 3D shape, reflection normal and transmission distortion of the automotive glass simultaneously. A stereo vision and an iterative algorithm based on the reflection law of the specular surface are utilized to obtain the 3D shape and reflection normal of the inspected part. Then, the bottom reflection of the glass is analyzed such that the line-shifting fringe pattern, based on step wave, is adopted. Additionally, the transmission distortion is defined as an angle between the incoming ray and the outgoing ray for the inspected automotive glass. The method proposed is simpler and more flexible than traditional methods. Finally, the system accuracy has been examined, with the results demonstrating its high accurate performance.
Optica Applicata, Vol. 40, 2010, nr 4, s. 827-841
Keywords: optyka; specular surface; quality inspection; transmission distortion